Penerapan Wahdatul Ulum Dalam Masyarakat - Fitri Randia Ningsih; Zaini Dahlan (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2023)
Wahdatul Ulum is the two main concepts in the philosophy of science at the State Islamic University of North Sumatra (UIN Sumut), which eventually merge into a broader framework of Wahdatul Ulum and become the driving force behind a philosophy. Wahdatul Ulum is typically used to create a concept that becomes more tangible and can solve human problems in society. The implementation of Wahdatul Ulum can be achieved through an interdisciplinary approach, usually involving research, education, and community service, so that the objectives set within this paradigm can be beneficial to the entire community and future generations. A graduate of the State Islamic University of North Sumatra Medan is expected to possess the character of Ulul Albab, including the personality of a servant of God, a broad ethnic perspective, a sense of happiness in contributing to society, a sense of responsibility, and possessing nine characteristics. Wahdatul Ulum plays a crucial role as the foundation for the university in producing qualified graduates with integrity, who are ready to make positive contributions to society and the nation in the future. This paradigm encourages collaboration and integration between various disciplines, allowing graduates to face the challenges of the time with a holistic understanding and a firm application of Islamic values in their lives.